Kinerja Organisasi Sektor Publik Dalam Mewujudkan Pelayanan Yang Efektif Pada Unit Pelayanan Bahasa Universitas Negeri Gorontalo - Sulila, Vivi Venti Vera; Igirisa, Irawaty (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
Penelitian ini bertujuan menganalisis kinerja organisasi sektor publik dalam mewujudkan pelayanan yang efektif This study aims to analyze public sector organizational performance in achieving effective services at the Language Service Unit of Universitas Negeri Gorontalo using the SERVQUAL approach. The study employed a quantitative approach with a descriptive research design. Data were collected through questionnaires distributed to service users consisting of students, lecturers, and the general public. Service quality analysis was conducted using the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that the quality of services at the Language Service Unit of Universitas Negeri Gorontalo was generally categorized as good. The reliability dimension obtained the highest mean score and was categorized as very good, while responsiveness, tangibles, assurance, and empathy were categorized as good. The findings suggest that service accuracy, staff responsiveness, service facilities, and communication competence were important aspects influencing service effectiveness at the Language Service Unit of Universitas Negeri Gorontalo. This study demonstrates that the SERVQUAL approach can be applied to measure service quality in academic support service units within higher education institutions.